Mathematical anxiety and the Zone of Proximal Development - Petakos, Kyriakos (EDiMaST: Experiences of Teaching with Mathematics, Sciences and Technology, 2019)
In the recent article mathematical anxiety in a group of junior students is discussed. These students have just entered tertiary education in the field of Hotel Management and have to deal with Business mathematics during their first semester. A question regarding mathematical anxiety is posed to them by the instructor. Their answers are written down and a sociocultural analysis ensues based on the renowned Vygotsky’s theory.